Persepsi Masyarakat Terhadap Branding Perpustakaan Jakarta: Studi Fenomenologi Peserta Acara Night at Library Volume 6 - Naurah Lisnarini; Dandi Saputra; Yanti Setiani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Branding is a strategy that aims to introduce and build an image to the target audience. The DKI Jakarta Regional Library, which is one of the public libraries, offers various information services and library facilities for the public. One of the library branding strategies is through the Night at Library program, an activity held at night in the library. This study aims to determine the perceptions of participants in the Night at Library Volume 6 event. The method used in this study is a qualitative approach with data collection techniques in the form of in-depth interviews and observations. Researchers conducted interviews with participants who participated in that event. The results of the study explained that participants had high enthusiasm for this event. According to participants, the event provided a unique experience while broadening their understanding of the services provided by the Jakarta Regional Library. Then, this event provided a different view of public perception because the library is not only seen as a reading and learning space but also as an interesting place able to provide entertainment. The Night at Library program has proven to be a new branding strategy for improving the image of the Jakarta Library. Through this activity, the library has succeeded in creating a unique experience that strengthens relationships with the community and increases public awareness of its services. Participation and appreciation show the potential for this program to be adapted and developed into an innovative and interactive branding model for other libraries.